Un caso de braquipterismo y observaciones en meroleuca (meroleucoides) dargei lemaire, 1982 (lepidoptera: saturniidae: hemileucinae) - González-Montana, Luis A.; Wilches-Álvarez, Winston (Instituto de Ecología, A.C., 2012)
Brachypterism cases are rarely reported in the literature, though, is a typical trait of life in certain taxa within Lepidoptera, for the above, is reported by the brachypterous female of the species Meroleuca (Meroleucoides) dargei, using as a host plant grass Penissetum clandestinum, an exotic species for Colombia. Finally was described aspects of the life cycle and morphology of the larvae.